Treatment of alcohol use disorder among people of South Asian ancestry in Canada and the United States: A narrative review. Issue 3 (3rd August 2020) - Puri, Nitasha; Allen, Kirsten; Rieb, Launette
Abstract: To explore access and treatment for alcohol use disorders (AUDs) among people of South Asian ancestry living in Canada or the United State, EQUATOR guidelines were applied to 34 manuscripts identified through an English language literature search (1946–2017) for this narrative review. The population studied has poor access to and engagement with treatment for AUD. Early evidence suggests benefit from adopting language-specific materials, offering South Asian–specific therapy groups, and incorporating traditional healers. Specific engagement and therapy considerations may increase AUD treatment access and effectiveness among South Asians living in Canada or the United States.